2000
DOI: 10.1021/tx000040g
|View full text |Cite
|
Sign up to set email alerts
|

Differential Destabilization of the DNA Oligonucleotide Double Helix by a T·G Mismatch, 3,N4-Ethenocytosine, 3,N4-Ethanocytosine, or an 8-(Hydroxymethyl)-3,N4-ethenocytosine Adduct Incorporated into the Same Sequence Contexts

Abstract: The T.G mismatch and the exocyclic adduct 3,N(4)-ethenocytosine (epsilonC) are repaired by the same enzyme, the human G/T(U) mismatch-DNA glycosylase (TDG). This enzyme removes the T, U, or epsilonC base from duplex DNA. The rate of cleavage was found to differ with the lesion and was also affected by neighbor sequences [Hang, B., Medina, M., Fraenkel-Conrat, H., and Singer, B. (1998) Proc. Natl. Acad. Sci. U.S.A. 95, 13561-13566]. Since sequence influences duplex stability, we determined the thermodynamic sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 33 publications
3
11
0
Order By: Relevance
“…Similar planar and sugar conformations of εC and 8-HM-εC can lead to the similar stacking potential of the modified base with the neighboring bases, and the ability to form a stable pair with the incorporated base, thus affecting replication efficiency and specificity. In another study on the thermodynamic stability of 15-mer duplexes with an εC or 8-HM-εC paired with G, both adducts showed similar destabilization of the double helix (35).…”
Section: Discussionmentioning
confidence: 90%
“…Similar planar and sugar conformations of εC and 8-HM-εC can lead to the similar stacking potential of the modified base with the neighboring bases, and the ability to form a stable pair with the incorporated base, thus affecting replication efficiency and specificity. In another study on the thermodynamic stability of 15-mer duplexes with an εC or 8-HM-εC paired with G, both adducts showed similar destabilization of the double helix (35).…”
Section: Discussionmentioning
confidence: 90%
“…In another study, 13 bp DNA duplexes containing a G ⅐ ⑀ C base pair were 13.4 -15.3 kcal/mol less stable than the parental G ⅐C-containing duplexes (38). A further study directly comparing the melting temperature of 15-bp DNA duplexes containing either a G ⅐ ⑀ C base pair or a G ⅐T mismatch found that the G ⅐ ⑀ C containing duplexes were 0.43-1.63 kcal/mol less stable than the corresponding G ⅐T-containing duplex (39). Interestingly, the difference in stability between G ⅐ ⑀ C and G ⅐T was greatest when the mismatch was in a CpG site.…”
Section: Discussionmentioning
confidence: 96%
“…34 The enthalpically stabilizing/entropically destabilizing effect of the dimer lesion is not a feature generally shared by base lesions. 24,3537 However, like many other lesions, the enthalpic and entropic effects tend to compensate for each other, leading to an overall modest change in free energy. 38 As demonstrated elegantly by the Breslauer group, structure and energetics need not relate directly, and a modest free change in the free energy of overall duplex formation might correspond to a large structural change or localized disturbances counterbalanced by the plasticity of the DNA structure.…”
Section: Discussionmentioning
confidence: 99%